Cows Get Crohn’s Disease and They’re Giving Us Diabetes - Coad Thomas Dow; Leonardo A Sechi (Microorganisms, 2019)
Increasingly, Johne’s disease of ruminants and human Crohn’s disease are regarded as the same infectious disease: paratuberculosis. Mycobacterium avium ss. paratuberculosis (MAP) is the cause of Johne’s and is the most commonly linked infectious cause of Crohn’s disease. Humans are broadly exposed to MAP in dairy products and in the environment. MAP has been found within granulomas such as Crohn’s disease and can stimulate autoantibodies in diseases such as type 1 diabetes (T1D) and Hashimoto’s thyroiditis. Moreover, beyond Crohn’s and T1D, MAP is increasingly associated with a host of autoimmune diseases. This article suggests near equivalency between paucibacillary Johne’s disease of ruminant animals and human Crohn’s disease and implicates MAP zoonosis beyond Crohn’s disease to include T1D.